Investigating Professionals’ Perceptions on the Software Supply Network Model in a Proprietary Educational Software Ecosystem - Malcher, Paulo; Feitosa, Rodrigo; Fernandes, Juliana Costa; Coutinho, Emanuel; Rivero, Luis; Viana, Davi; Santos, Rodrigo Pereira dos (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2026: Anais do XXII Simpósio Brasileiro de Sistemas de Informação, 2026)
Research Context: Modeling helps understand the structure, actors, and interactions in software ecosystems (SECO). The software supply network (SSN) is one of the best-known SECO modeling notations. In a previous study, we proposed an SSN model for a proprietary educational SECO, namely the SOLAR SECO, and identified the need to analyze this SSN model from the professionals’ perceptions. Scientific and/or Practical Problem: The practical use of SSN models is still poorly explored, and little is known about how professionals perceive and apply them in real SECO. Proposed Analysis: This work analyzes this SSN model based on professionals’ perceptions to identify issues and challenges. Related IS Theory: Socio-technical Theory, which explains the way the interaction between social and technical elements affects professionals’ perceptions and use of artifacts, such as the SSN model. Research Method: We applied a questionnaire and conducted semi-structured interviews, analyzing the responses qualitatively. Summary of Results: Professionals perceived the model as useful for visualizing actors and supporting communication, but not for identifying new functionalities. Contributions and Impact to IS area: This study offers empirical evidence and a methodological procedure to support modeling and analysis of other SECO cases.